A Cross-National Survey of People Living with Hemophilia: Impact on Daily Living and Patient Education in Central Europe - Banchev, Atanas; Batorova, Angelika; Faganel Kotnik, Barbara; Kiss, Csongor; Puras, Gediminas; Zapotocka, Ester; Zupancic-Salek, Silva; Patient Advocacy Group (Patient preference and adherence, 2021)
BACKGROUND: Information about the impact of hemophilia on daily living and information preferences for patients and their caregivers in Central Europe has been limited. METHODS: This cross-national survey was conducted between April 1 and October 15, 2020 and utilized a self-administered questionnaire to collect data (Typeform™) from people living with hemophilia in Bulgaria, Croatia, Czech Republic, Hungary, Slovakia and Slovenia. The questionnaire included 22 questions regarding difficulties in daily life and preferences for receiving hemophilia-related information. Respondents were stratified into two main groups, people with hemophilia (PwH) or their caregivers (CPwH). Results were analyzed using descriptive statistics. RESULTS: Of the 364 respondents, 232 were PwH (63.7%) and 132 were CPwH (36.3%). In total, 70.3% of hemophilia patients/caregivers responded that they are kept sufficiently informed about life with hemophilia, with 68.0%, 59.1% and 56.3% of respondents obtaining information from their physicians, patient associations and via digital media (internet and social media), respectively. However, 97.8% of respondents expressed an interest in additional information, particularly new hemophilia treatment options (62.1%), which in contrast to other topics was indicated most frequently by both patients and caregivers in all six countries. Most frequent difficulties in everyday life with hemophilia were identified as mobility problems (41.8%), unexpected bleeding (38.5%), pain (35.4%), and uncertainty with what they can or cannot do (25.0%). During the 2020 COVID-19 pandemic, 52.5% of respondents reported that they did not experience any major change in daily living with hemophilia. CONCLUSION: Based on our Central European survey, hemophilia mostly affects peoples' lives by causing mobility difficulties, unexpected bleeding, pain and uncertainty in daily activities. Although the majority of respondents reported being educated about hemophilia, most PwH and CPwH respondents sought additional information, highlighting the need for continuous personalized patient education to cope with present challenges.
Keywords: cross-national survey; information sources; patient preference; Central Europe; hemophilia